Effect of anti-inflammatory drugs on the storm of inflammatory factors in respiratory tract infection caused by SARS-CoV-2: an updated meta-analysis - Qin, Zhiping; Li, Yongbiao; Sun, Wenjing; Lu, Yangyang; Zhang, Nana; Yang, Rongfei; Liu, Yiting; Tang, Li; Liu, Qingshan (Frontiers in Public Health, 2023)
Background: New reports suggest that anti-inflammatory drugs are widely used to treat respiratory tract infections caused by SARS-CoV-2. Anti-inflammatory drugs were the most frequently used treatment for the COVID-19-related cytokine storm in China. However, the efficacy of anti-inflammatory drugs has yet to be systematically analyzed, and clinicians are often uncertain which class of anti-inflammatory drug is the most effective in treating patients with respiratory tract infections caused by SARS-CoV-2, especially those with severe disease. Methods: From 1 October 2022, relevant studies were searched in the PubMed, Embase, Medline, Cochrane Library, and Web of Science databases. A total of 16,268 publications were retrieved and collated according to inclusion and exclusion criteria, and sensitivity analyses were performed using STATA 14 software. Publication bias was assessed using funnel plots and Egger's test. Study quality was assessed using the PEDro scale, and the combined advantage ratio was expressed as a 95% confidence interval (CI). In total, 19 randomized controlled trials were included in the study. STATA 14 software was used for all random effects model analyses, and the results are expressed as relative risk ratios (RR) with 95% CI. Results: Quantitative analyses were performed on 14,514 patients from 19 relevant randomized controlled clinical trials. Pooled estimates (RR=0.59, 95% CI 0.44-0.80) revealed that the use of anti-inflammatory drugs resulted in a significant reduction in mortality in patients with respiratory tract 2 infection caused by SARS-CoV-2 compared with controls, and methylprednisolone (RR=0.14, 95% CI 0.03-0.56) was more effective than other anti-inflammatory drugs.Anti-inflammatory drugs were effective in reducing mortality in critically ill patients (RR=0.67, 95% CI 0.45-0.98) compared with non-critically ill patients (RR=0.50, 95% CI 0.34-0.76); however, more clinical evidence is needed to confirm these findings. Conclusion: The use of anti-inflammatory drugs in patients with respiratory infections caused by SARS-CoV-2 reduces patient mortality, especially in severe cases. In individual studies, methylprednisolone was more effective than other drugs.